2017
DOI: 10.1007/s00404-017-4297-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between vaginal and sublingual misoprostol 50 µg for cervical ripening prior to induction of labor: randomized clinical trial

Abstract: NCT02732522. Registry website: https://clinicaltrials.gov/ .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…This low frequency of meconium in the amniotic fluid may be a consequence of the low dose of medication used. The median first-and fifth-minute Apgar scores were the same in both groups and similar to those reported in a study conducted in Uruguay [26].…”
Section: Discussionsupporting
confidence: 87%
“…This low frequency of meconium in the amniotic fluid may be a consequence of the low dose of medication used. The median first-and fifth-minute Apgar scores were the same in both groups and similar to those reported in a study conducted in Uruguay [26].…”
Section: Discussionsupporting
confidence: 87%
“…However, a recent PROBAAT‐II multicenter Dutch study by Eikelder et al . and Uruguay study by Conde et al . used similar (50 μg) dose.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 103 trials identified, just 63 were RCTs. 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 The majority of RCTs were single-center trials conducted in academic hospitals, which can limit the generalizability of the results to other community-based populations. Among the 12 multicenter trials, the number of centers ranged from 2 to 49 and tended to include both university-affiliated and community hospitals.…”
Section: Limitations Of Trials On Labor Inductionmentioning
confidence: 99%